Profiles of traditional farms: soil texture, total inorganic N and bacteria-producing estate - Hastuti, Yuni Puji; Rusmana, Iman; Widiyanto, T. (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
Pond traditional system is the pond in still activity with a symple management system. This activity indicated by low technology and relatively low production level. Aquaculture activities in traditional pond not loss from nitrification and denitrification prosess, however this process is more low production rather than semiintensive and intensive system. This study aims to observe abundance of bacteria nitrification along with changes soil texture, and N-organic in the soil of traditional pond. Chemical and biological analyses were done using spectroscopy and Most Probable Number methods to determine the amount of nitrite and ammonium production of bacteria. Based of the result, each stratum traditional ponds have relatively similar abundance in nitrite producing bacteria of 7.08-7.47 Log CFU/g. Increasing abundance in ammonium producing bacteria was found in all stratum, range from 5.63 Log cfu/g to 8.12 Log cfu/g. From the first day of preparation, traditional ponds have a lot of nitrite and ammonium producing bacteria.Keywords: traditional, pond, nitrification, abundance of bacteri. ABSTRAKTambak sistem tradisional merupakan tambak yang dalam kegiatannya masih menggunakan sistem manajemen sederhana. Hal ini ditandai dengan penerapan teknologi sederhana, dan tingkat produksi relatif rendah. Kegiatan budidaya di tambak tradisional tidak akan terlepas dari proses nitrifikasi dan denitrifikasi, namun demikian proses ini relatif lebih rendah aktivitasnya daripada tambak sistem semiintensif dan intensif. Tujuan dari penelitian ini adalah mempelajari kelimpahan bakteri penghasil senyawa nitrit, amonium seiring dengan perubahan tekstur tanah, dan N-organik pada tanah tambak tradisional. Media pertumbuhan bakteri dikondisikan bebas oksigen (oxygen free nitrogen/OFN method) , sedangkan kelimpahan bakteri dianalisis dengan rumus most porbable number (MPN). Berdasarkan hasil, setiap strata tanah tambak tradisional memiliki jumlah bakteri penghasil nitrit yang relatif sama, yaitu antara 7,08-7,47 Log cfu/g. Peningkatan kelimpahan bakteri penghasil amonium terjadi pada semua strata, yaitu berkisar antara 5,63 Log cfu/g sampai dengan 8,12 Log cfu/g. Dari hari pertama persiapan, tambak tradisional telah memiliki kelimpahan bakteri penghasil nitrit dan amonium yang berlimpah.Kata kunci: tradisional, tambak, nitritifikasi, kelimpahan bakteri.